The Climatological Effect of Perturbations in Atmospheric Burden and Optical Properties of Saharan Dust - Strong, Jeffrey Davin O'Neill (Princeton, NJ : Princeton University, 2016)
Mineral dust aerosols are a diverse set of atmospheric constituents which provide some of the largest natural direct radiative forcing and have the propensity to affect several human-relevant issues. This dissertation investigates the regional and global climatic response to aerosol radiative forcing from dust using simulations with a suite of fully coupled climate models. An idealized perturbation to global dust climatology, with changes in Saharan-born dust comparable to the observed changes between the 1960s and 1990s, and an ensemble of realistic dust optical properties are utilized to study the climatological effect of perturbations in atmospheric burden and optical regime of Saharan dust. Changes in dust atmospheric concentration lead to direct radiative responses from the top of the atmosphere (ToA) through to the surface along with regional hydrologic and thermodynamic responses, depending crucially on the amount of aerosol absorption versus scattering. There are large anomalies in the West African monsoon due to moist enthalpy changes throughout the atmospheric column over West Africa. In the tropical North Atlantic, there are significant responses in the upper ocean heat budget arising from the wind stress curl response to a shift in the Atlantic Intertropical Convergence Zone and associated mixed layer depth anomalies. Simultaneously, there are changes in tropical cyclone activity across the North Atlantic Ocean with the largest response occurring in the most absorbing and scattering optical regimes. There are also non-negligible anomalies in the North Pacific and Indian Oceans. A relationship between accumulated cyclone energy and ToA radiative flux anomalies is used to explain the North Atlantic anomalies while several known climate variations are theorized to explain the far-field response to the dust forcing. Changing the optical regime of dust alone is found to lead to radiative anomalies larger than simply adding dust. As dust becomes more scattering, there is a net global cooling focused in the Northern Hemisphere and a general equatorward shift of tropical precipitation and the mid-latitude atmospheric jets. This leads to a preferential negative phase of the North Atlantic Oscillation, a decrease in the Atlantic Meridional Overturning Circulation, and associated changes to the global meridional heat transport.